Latihan Berjalan dengan Kontrol Pernapasan pada Penderita Penyakit Paru Obstruktif Kronik (PPOK): Studi Fenomenologi - Orita Satria; Dewi Elizadiani Suza; Mula Tarigan (Journal of Telenursing (JOTING), 2022)
This study aims to explore the experience of walking exercise with breathing control in COPD patients. The method used is qualitative with a descriptive phenomenological approach. Participants in this study amounted to 15 people with COPD. Data obtained from in-depth interviews, then analyzed using the Colaizzi method. The results showed that five themes were identified, namely: 1) the implementation of walking exercises with breathing control; 2) increased physical activity and quality of life; 3) increase oxygen demand and reduce shortness of breath; 4) reduce anxiety and improve sleep quality; and 5) family support. In conclusion, walking and breathing exercises are good exercise choices for COPD because they can meet oxygen needs, reduce shortness of breath, reduce anxiety and stress in COPD. Keywords: Breathing Control, Walking Exercise, COPD